2019
DOI: 10.1039/c8py01648h
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched poly(ethylenimine-co-oxazoline) by thiol–yne chemistry for non-viral gene delivery: investigating the role of polymer architecture

Abstract: Synthesis of long-chain hyperbranched poly(ethylenimine-co-oxazoline)s by AB2 thiol–yne chemistry is reported, and their application as pDNA transfection agents studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 58 publications
1
47
0
Order By: Relevance
“…185,186 In a recent study, we reported the synthesis of hyperbranched poly(ethyleneimine-co-oxazoline) by combination of thiol-yne photoaddition chemistry with well-defined linear ethyleneimine-co-oxazoline copolymers (Figure 7). 126 This new PEI hyperbranched architecture with only secondary amines (compared to bPEI with primary, secondary, and tertiary amines) was used to complex and deliver plasmid DNA coding for GFP. In vitro toxicity assays and gene transfection experiments with HEK293T cell-line, highlighted the impact of polymer architecture, as the hyperbranched structure showed lower toxicity but similar transfection efficiencies compared to the equivalent linear p(ethyleneimineco-oxazoline) copolymers.…”
Section: Long Chain Hyperbranched Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…185,186 In a recent study, we reported the synthesis of hyperbranched poly(ethyleneimine-co-oxazoline) by combination of thiol-yne photoaddition chemistry with well-defined linear ethyleneimine-co-oxazoline copolymers (Figure 7). 126 This new PEI hyperbranched architecture with only secondary amines (compared to bPEI with primary, secondary, and tertiary amines) was used to complex and deliver plasmid DNA coding for GFP. In vitro toxicity assays and gene transfection experiments with HEK293T cell-line, highlighted the impact of polymer architecture, as the hyperbranched structure showed lower toxicity but similar transfection efficiencies compared to the equivalent linear p(ethyleneimineco-oxazoline) copolymers.…”
Section: Long Chain Hyperbranched Polymersmentioning
confidence: 99%
“…a) Hyperbranched p(ethyleneimine-co-oxazoline), with varying ethyleneimine contents from 32% to 78%, by thiol-yne chemistry for use in the delivery of plasmid DNA with a GFP reporter gene, b) polymer toxicity as determined by XTT assay in HEK293T cells, c) proportion GFP positive cells and mean fluorescent intensities of transfected HEK293T cells compared to commercial branched PEI. Figure adapted with permission126 . Copyright 2019 Royal Society of Chemistry.…”
mentioning
confidence: 99%
“…Like dendrimers, HBPs form cavities that can be used to encapsulate cargos of different sizes [118] including small chemotherapeutic drugs such as DOX, [119,120] camptothecin (CPT), [121,122] cisplatin, [123][124][125] [127][128][129][130] and siRNA [131][132][133] form complexes with unimolecular HBPs such as branched poly(ethylene imine) (PEI) [134] by electrostatic interactions. Tuning the structure of HBPs permits to control the strength of the interaction between gene and carrier by modulating the charge density at its surface, adjusting its molecular weight, and preparing different molecular structures.…”
Section: Drug Loadingmentioning
confidence: 99%
“…Polyethylenimine (PEI) is the most studied cationic polymer for gene delivery, and branched PEI 25 kDa has been considered as the golden standard for new polymeric non-viral vectors on account of its high transfection efficiency (TE), which is attributed to the strong buffering capacity in the pH range of 7.4-5.1 [9]. Although high molecular weight PEI shows good TE, it also exhibits obvious cytotoxicity for its non-degradable and highly positively charged structure [10,11]. Reducing molecular weight could solve the toxicity problem, but the TE is sacrificed [12].…”
Section: Introductionmentioning
confidence: 99%